ALDOL CONDENSATION OF N-ALKYLATED-3-ARYL-4,6-DIMETHOXY-7-FORMYLINDOLES AS A GOOD METHOD FOR THE SYNTHESIS OF 1-ARYL-6,8-DIMETHOXYPYRROLO[3,2,1-hi]INDOLE-4-CARBOXYLATES - Jumina Jumina (Indonesian Journal of Chemistry, 2006)
Alkylation of 3-aryl-4,6-dimethoxyindole 3a and 3b with methyl and ethyl a-bromoacetates afforded good yields of indol-1-ylacetates 4. Treatment of these indoles 4 with the Vilsmeier formylation reagent gave formylindoles 5 in 54-81 % yield. These formylindole 5 underwent intramolecular aldol condensation when treated with sodium hydride in tetrahydrofuran to give pyrroloindole-4-carboxylates 6 in 30-60 % yield. Structural assignment based on spectroscopic data confirmed the structure of the synthesized pyrroloindoles. In the case of pyrroloindole 6c, the structure of this molecule was also proven by X-ray crystallography data.